EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH PADA KANTOR RUMAH SAKIT UMUM DAERAH KABUPATEN MAMUJU - Zamrudiah, Zamrudiah (LPPM Universitas Muhammadiyah Mamuju, 2020)
The purpose of this study is to examine more deeply the effectiveness of the Regional Financial Management at the Regional General Hospital Office in Mamuju Regency. Informants were selected from several related agencies. The data used are data regarding Planning, Implementation / Administration, Responsibility and Supervision. The technique used is in-depth interviews using structured interview guidelines, then the data obtained describe. The results showed that the management of regional finances in the Mamuju Regency Regional General Hospital office had not been effective given the lack of Human Resources and experience. As for the Government Accounting Standards system, it cannot yet be implemented in full, not only the Mamuju Regency Regional General Hospital, but almost all other agencies also do not have accountants. While the existing system refers to Government Accounting Standards known as SAP. The above system was implemented in 2007 but the results were not as expected. So the researchers concluded that all financial managers should have a minimum background in reliable Economics and Accounting Education, as well as the completeness of facilities and infrastructures and a conducive environment that also supports the achievement of effective and efficient financial management.